GEOMETRI EUCLID EG(2, pn) UNTUK MEMBENTUK RANCANGAN BLOK TIDAK LENGKAP SEIMBANG - Irawanto, Bambang; Hidayati, Yuni (MATEMATIKA, 2007)
﻿﻿A Balanced Incomplete Block (BIB) design with parameters is an arrangement of v distinct objects into b bloks such that each block contains exactly k distinct objects, each object occurs in exactly r different blocks, and every pair of distinct object occurs together in exactly l blocks. Euclidean geometry EG (2, pn) is the finite geometry of two dimensions over the Galois Field GF(pn). By considering that the object of BIB design is same with the points of EG(2, pn) and the blocks which contain those objects are same with the lines which contain the points from EG(2, pn), EG (2, pn) can be used to construct BIB design.